LEGAL ACCOUNTABILITY OF PUBLIC ACCOUNTANTS IN THE FINANCIAL STATEMENT BASED ON INDONESIA'S LEGAL SYSTEM - Raja Sirait; Made Warka; Krisnadi Nasution; Otto Yudianto (Yustisia, 2018)
The purpose of this study is to examine further regarding the legal accountability of the public accountants on financial statements in the Indonesian legal system. This research is important to conduct due to the public accounting profession that has a significant role to express opinions about fairness in all material matters, financial position, results of operations, changes in equity, and cash flows in accordance with general accounting principles accepted in Indonesia. In other words, the responsibility of public accountants is to express opinions on financial statements. Public accountants are responsible for planning and carrying out audits in order to obtain adequate assurance about whether the financial statements are free from material misstatement, whether caused by errors or fraud. Financial statements are the responsibility of management, and the public accounting profession cannot just be punished. This research is a normative legal research. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection techniques use literature study, while data validation techniques use source criticism. The data is analyzed by using legal interpretation methods to obtain answers to the questions examined. The results show that a public accountant can have criminal and civil liability in carrying out the duties when publishing a company's financial statements.